Motivational Factors that Influence Student Work Attitude - Kasa, Zakaria; Mccracken, J. David (Universiti Putra Malaysia Press, 1994)
Employers look for employees who have positive work attitudes besides technical knowledge and related skills. Students, therefore, should have positive work attitudes to be successful in the workplace. This study is an attempt to identify the motivational factors that may be associated with work attitudes of students at Universiti Pertanian Malaysia. The motivational factors include: (1) educational aspirations, (2) occupational aspirations, (3) reason for entering the programme, (4) religiosity, and (5) student perception of parental work values. A cluster random sampling was used to determine the sample of respondents. The sample consisted of686 diploma programme students. The results indicated that the reason for entering the programme, religiosity and student perception of parental work values were related to work attitude. These variables were further analyzed to determine the semi-partial multiple regression coefficients. The findings showed that reason for entering the programme did not account for a significant unique proportion of the variance in work attitude. However, religiosity and student perceptions of parental work values accounted for a significant unique proportion of the variance in work attitude. These two variables were used in the stepwise multiple regression analysis. It was found that the two variables were the best predictors of the work attitude of diploma programme students at the Universiti Pertanian Malaysia.